Biyahe - Castro, Robbiellette V.
If I were to define my thesis in one phrase, it would be this: "A glimpse at a young man's journey in life." Entitled "Biyahe," my thesis is in narrative format and runs for approximately 14 minutes. I utilized the use of the montage technique and preferred to make the entire narrative in black and white primarily for two reasons. First is to dramatize that the events took place in the past and second is to create and achieve that film look despite of its being in Video 8 format. "Biyahe" is inspired by the story of my boyfriend, Seth - an only child who never new his father since birth. Throughout his life, he felt he was empty and so he joined an organization, which offers friendship, and most importantly, brotherhood. However, he did not get through. The men he thought were his "brothers" beat him to death. He died on the last initiation night. Seth's dreams were never fulfilled. His hopes flew and never will they return. But for me and for all the people, who knew Seth in one way or another, believe because of his thirst for the love of a stranger - his unknown father. The father he never saw haunted his young life. If only Seth knew that the man he tried too find all his life was not worthy of his affections. My thesis is not just about Seth. It is for him, for his journey, for his dreams...